Impact of autoimmune gastritis on chronic urticaria in paediatric patients - pathophysiological point of views - Bufka, J; Sýkora, J; Vaňková, L; Gutová, V; Kačerová, Š; Daum, O; Schwarz, J (European journal of pediatrics, 2024)
UNLABELLED: We would like to provide an updated comprehensive perspective and identify the components linked to chronic spontaneous urticaria (CSU) without specific triggers in autoimmune atrophic gastritis (AAG). AAG is an organ-specific autoimmune disease that affects the corpus-fundus gastric mucosa. Although we lack a unified explanation of the underlying pathways, when considering all paediatric patients reported in the literature, alterations result in gastric neuroendocrine enterochromaffin-like (ECL) cell proliferation and paracrine release of histamine. Several mechanisms have been proposed for the pathogenesis of CSU, with much evidence pointing towards AAG and ECL cell responses, which may be implicated as potential factors contributing to CSU. The excessive production/release of histamine into the bloodstream could cause or trigger exacerbations of CSU in AAG, independent of Helicobacter pylori; thus, the release of histamine from ECL cells may be the primary modulator. CONCLUSION: Considering the understanding of these interactions, recognising the respective roles of AAG in the pathogenesis of CSU may strongly impact the diagnostic workup and management of unexplained/refractory CSU and may inform future research and interventions in the paediatric population. WHAT IS KNOWN: • Autoimmune atrophic gastritis is a chronic immune-mediated inflammatory disease characterised by the destruction of the oxyntic mucosa in the gastric body and fundus, mucosal atrophy, and metaplastic changes. • Autoimmune atrophic gastritis in paediatric patients is important because of the poor outcome and risk of malignancy and possibly underestimated entities primarily reported in single-case reports. WHAT IS NEW: • Upper gastrointestinal inflammatory disorders, independent of H. pylori, have been implicated as potential inducing factors in the development of chronic spontaneous urticaria. • If a paediatric patient presents with symptoms such as anaemia, reduced vitamin B12 levels, recurrent urticaria with no other detectable aetiology, positive anti-parietal cell antibodies, and elevated gastrin levels, autoimmune atrophic gastritis should be considered a possible cause of chronic urticaria.
Keywords: Chronic urticaria; chronická urtikarie; Helicobacter pylori; Paediatrics; dítě; žaludeční sliznice; Autoimmune Diseases; Gastric Mucosa; lidé; Gastritis; Histamine; Autoimmune gastritis; Pathophysiology; Chronic Urticaria; autoimunitní nemoci; histamin; Gastritis, Atrophic; chronická nemoc; Child; gastritida; Helicobacter Infections; Chronic Disease; infekce vyvolané Helicobacter pylori; gastritida atrofická; Humans